Konseling Kelompok Teknik Self-Management untuk Mengurangi Prokrastinasi Akademik Siswa - Mekris Yohanes Nenoliu; Maria Natalia Loban; Merita Florawati Naisanu (Scidacplus, 2026)
This study aims to determine the effectiveness of group counseling using self-management techniques in reducing academic procrastination among students at SMP Negeri 20 Kupang. The type of research used is quantitative research with an experimental method (one group pre-test post-test design). Data collection techniques used a Likert scale by distributing questionnaires to eighth-grade students with 30 items. The population, consisting of 85 people, showed that the students' procrastination behavior profile was in the high category at 59%. The sample, consisting of 5 students, was given treatment through group counseling using self-management techniques. The results indicated a difference in pre-test scores of 81% and post-test scores of 54%, resulting in a total decrease of 27%. The normality test results were 0.434 for the pre-test and 0.111 for the post-test, both greater than (Sig > 0.05). It is concluded that group counseling using self-management techniques is normally distributed. The hypothesis test using the t-test showed t-table < t count = 2.776 < 10.726. There was a change in students' behavior in completing assignments on time, their enthusiasm for learning, prioritizing task completion, being calm, and confident. Based on the research results, it was found that the implementation of group counseling using self-management techniques is effective in reducing academic procrastination among students at SMP Negeri 20 Kupang.